2022
DOI: 10.3389/fimmu.2022.974767
|View full text |Cite
|
Sign up to set email alerts
|

Improved induced innate immune response after cART initiation in people with HIV

Abstract: IntroductionImpairment of the innate immune function may contribute to the increased risk of bacterial and viral infections in people with HIV (PWH). In this study we aimed to investigate the induced innate immune responses in PWH prior to and after initiation of combinational antiretroviral therapy (cART). Furthermore, we aimed to investigate if the induced innate immune responses before initiation of cART were associated with CD4+ T-cell recovery one year after initiating cART.Material and methodThe induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The TruCulture® assay has been described previously ( 15 , 16 , 24 ). In brief, 1 mL of whole blood was transferred into four TruCulture® tubes (Myriad RBM, Autin, TX, USA) within one hour of sampling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TruCulture® assay has been described previously ( 15 , 16 , 24 ). In brief, 1 mL of whole blood was transferred into four TruCulture® tubes (Myriad RBM, Autin, TX, USA) within one hour of sampling.…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies only assessed CMV-specific immunity. Interestingly, a new commercially available and highly standardized method (TruCulture®) to asses overall immune function has been investigated in other settings and may be used in SOT recipients ( 15 17 ). We hypothesized that individual immune function contributes to the observed differences in the risk of herpes virus infections.…”
Section: Introductionmentioning
confidence: 99%
“…Combining whole blood stimulation with longitudinal sampling of patients has been used to monitor changes in responsiveness over time with regard to disease progression and treatment‐induced effects. For example, longitudinal sampling before and during treatment was performed to study innate immune function during different cancer treatments [63] and combinational antiretroviral therapy in HIV [64]. Further, longitudinally sampling COVID‐19 patients from admission to the hospital until dismissal (or death) revealed that lower release of IL‐1β upon LPS as well as IL‐12 and IL‐17A upon R848 stimulation at admission were associated with more severe disease at peak severity [65].…”
Section: Clinical Applications Of Whole Blood Stimulationmentioning
confidence: 99%